Melacak Otentisitas Hukum Islam Dalam Hadis Nabi (Studi Pemikiran Josepht Schacht) - Muhtador, Mohammad (AL QUDS : Jurnal Studi Alquran dan Hadis, 2017)
This article researche Joseph Schacht’s idea of Islamic law. As an orientalâ€™s, Schacht has competence in studying Islamic law with history perspective. Schacht’s study of Islamic law on the basis of skepticism by historical criticism is a collection of analyzes in the study of the hadith of the Prophet. The conclusion is different from other thinkers. Schacht doubts the authenticity of Islamic law as a product of teaching, the article of Islamic law development cannot be separated from the interests of the ruler.